Chikungunya outbreak in Bangladesh (2017): sociodemographic and clinical characteristics of patients from three hotspots - Mohammad Robed Amin; Mohammad Jahid Hasan; Md. Abdullah Saeed Khan; Md Abdur Rafi; Rafiqul Islam; Tarek Shams; Mohammed Jahedul Islam; Abu Saif Mohammad Lutful Kabir; Mohiuddin Sharif; David Gozal (Tropical Medicine and Health, 2022)
Abstract Background Chikungunya is a severely debilitating disease. Bangladesh witnessed one of the largest outbreaks in 2017. Here, we described the clinical profile of the chikungunya outbreak in Bangladesh and its heterogeneity across three hotspots. Methods This was a descriptive cross-sectional study of 432 individuals interviewed from the outpatient department of three study sites (Dhaka, Chittagong, and Sitakundu Upazilla of Bangladesh) after confirmation by the study physicians. Both laboratory-confirmed cases and probable cases were recruited between July and October 2017. Results Of all, 18% (79) were laboratory confirmed, and 353 82% (335) were probable cases. The male:female ratio was almost equal (1.09:1), and the predominant age group was 18–59 years. The mean age of the presentation was 36.07 ± 13.62 (SD) years. Fever and arthralgia were the most common presentations and were present in > 95% of cases. Other frequent symptoms were fatigue, myalgia, headache, nausea, and vomiting. Approximately half of the patients had arthritis and erythematous rash. Arthritis was predominant in Chittagong city, while maculopapular rash was not observed in Sitakunda city. However, fatigue, nausea, and vomiting are more common among patients in Dhaka city. Significant heterogeneity of clinical manifestations was present across the three hotspots (p < 0.05 for all). Both confirmed and probable cases shared similar characteristics except muscle ache (p = 0.22) and rash (p = 0.37). Conclusion The clinical profile of chikungunya virus-induced disease displays significant location-related heterogeneity in Bangladesh during a large outbreak. Although the causes of such differences are unclear, improved public and medical personnel education on this condition may lead to earlier diagnosis and treatment.